1994
DOI: 10.1111/j.1745-4530.1994.tb00327.x
|View full text |Cite
|
Sign up to set email alerts
|

MOISTURE SORPTION STUDY ON NIGERIAN FOODS: MAIZE and SORGHUM

Abstract: Adsorption-desorption behavior of maize and sorghum between a, = 0.10 -0.98 at temperatures of 20, 25 and 40C was studied. The grains exhibited type I1 sorption isotherm. The sorption data were analyzed using six sorption models and the coeflcients of determination were between 0.6965-0.9994. The Caurie model gave the poorest fit and the Henderson model the best. Some models were better for adsorption than for desorption. The GAB and BET monolayer moisture contents were not significantly @ > 0.05) different. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
1
13
0
7
Order By: Relevance
“…So, it is possible that an exothermic reaction decreases as the temperature increases. Similar results also were obtained in some other studies (Achoba, Elegbede, Agbaji, & Agbaji, 1991;Andrieu et al, 1986;Ayrancı, Ayrancı, & Dogantan, 1990;Certel & Ertugay, 1997;Chen, 2003;Debnath et al, 2002;Igbeka & Blaisdel, 1982;Inglett & Munck, 1980;McMinn & Magee, 1999;Rovedo, Roberto, & Constantino, 1993;Sopade & Ajisegeri, 1994;Tsami, Marinos-Kouris, & Maroulis, 1990). Moisture sorption of semolina and farina increased with increasing a w value but that sharply increased after 0.75a w .…”
Section: Sorption Isothermssupporting
confidence: 88%
See 1 more Smart Citation
“…So, it is possible that an exothermic reaction decreases as the temperature increases. Similar results also were obtained in some other studies (Achoba, Elegbede, Agbaji, & Agbaji, 1991;Andrieu et al, 1986;Ayrancı, Ayrancı, & Dogantan, 1990;Certel & Ertugay, 1997;Chen, 2003;Debnath et al, 2002;Igbeka & Blaisdel, 1982;Inglett & Munck, 1980;McMinn & Magee, 1999;Rovedo, Roberto, & Constantino, 1993;Sopade & Ajisegeri, 1994;Tsami, Marinos-Kouris, & Maroulis, 1990). Moisture sorption of semolina and farina increased with increasing a w value but that sharply increased after 0.75a w .…”
Section: Sorption Isothermssupporting
confidence: 88%
“…Physical adsorption on microporous solids can result in type II isotherms, and correspond to multilayer formation (Adamson, 1990). Therefore, these sorption isotherm curves of the samples indicated that sorption occurred in semolina and farina, starchy products, was multilayer adsorption Sopade & Ajisegeri, 1994).…”
Section: Sorption Isothermsmentioning
confidence: 95%
“…The limited number of observations may explain this poor fitting. Since BET equation is reported to be one of the most suitable models to describe the sorption behaviour of starchy foods (Sopade and Ajisegeri 1994;Al-Muhtaseb et al 2002), it seems reasonable that it doesn't suit to describe freeze dried whey-grape powder. However Arslan and Togrul (2000) found this equation also suitable for moisture isotherms of tea.…”
Section: Resultsmentioning
confidence: 99%
“…son mayores con respecto a los obtenidos con la ecuación de BET (X m = 0,042-0,079 g agua/ g m.s. ); resultados similares obtuvieron SOPADE & AJISERIGI [25] y TIMMERMANN et al [26], para granos y afrecho de maíz, respectivamente, reportando que la humedad de la monocapa para los modelos GAB y BET no son similares. Por otra parte, en la misma tabla se muestra la tendencia a disminuir del contenido de humedad de la monocapa (X m ) al aumentar la temperatura, lo que puede deberse a la menor disponibilidad de los sitios activos (o enlaces de hidrógeno) en los polímeros de almidón para la unión con el agua [29].…”
Section: -Modelado De Las Isotermasunclassified
“…La ecuación de Henderson también ajustó correctamente los datos de humedad experimental para todo el rango de actividad de agua, y su utilización es adecuada para alimentos con alto contenido de almidón [25]. La utilización de la ecuación de Caurie es de importancia en el modelado de isotermas de alimentos deshidratados, ya que nos entrega el parámetro llamado "contenido de humedad de seguridad" (X S ), que indica el contenido de humedad al cual se lograría la máxima estabilidad del alimento durante su almacenamiento.…”
Section: -Modelado De Las Isotermasunclassified